A worthy heart - Mason, Susan Anne (Mason, Susan Anne. Courage to dream, 2016)
Maggie Montgomery arrives in America from Ireland under the premise of visiting family, but really, she intends to stay in the Land of Opportunity, and soon she meets Adam, a black sheep whose past may come in the way of their love.